2021
DOI: 10.1111/1755-0998.13444
|View full text |Cite
|
Sign up to set email alerts
|

Opening a next‐generation black box: Ecological trends for hundreds of species‐like taxa uncovered within a single bacterial >99% 16S rRNA operational taxonomic unit

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…3h). A shift in bacterial ecotype diversity along a calcium gradient was previously reported (Hahn et al, 2021), but how calcium directly influences community composition is unclear. Perhaps the effect is indirect and calcium influences ecological interaction in the plankton community, as low calcium levels were previously shown to limit zooplankton productivity and diversity (Azan & Arnott, 2018).…”
Section: Lake Conditions Shape the Structure And Function Of Bacteria...mentioning
confidence: 87%
“…3h). A shift in bacterial ecotype diversity along a calcium gradient was previously reported (Hahn et al, 2021), but how calcium directly influences community composition is unclear. Perhaps the effect is indirect and calcium influences ecological interaction in the plankton community, as low calcium levels were previously shown to limit zooplankton productivity and diversity (Azan & Arnott, 2018).…”
Section: Lake Conditions Shape the Structure And Function Of Bacteria...mentioning
confidence: 87%
“…Furthermore, an approximate boarder between habitats characterized by water with low Ca 2+ (<12 mg l −1 Ca 2+ ) and high Ca 2+ concentration (>12 mg l −1 Ca 2+ ) is indicated. It has been shown that planktonic Polynucleobacter species either prefer low or higher Ca 2+ concentrations [19]. The numbers identifying the respective type strains can be found in .…”
Section: Ecology and Biogeographymentioning
confidence: 99%
“…Thus, it has to be assumed that all 14 proposed type strains represent free-living, planktonic freshwater bacteria, but distinct ecological adaptations of the strains have to be expected. Further knowledge on the ecology of the proposed species and biogeographical aspects can be gained from a previously published amplicon sequencing study [19] and from previously published metagenome data [52] characterizing bacterioplankton of a lake representing the home habitat of two type strains described here. [34]); 3, P. sinensis MWH-HuW1 T (data from [18]); 4, P. aenigmaticus MWH-K35W1 T (data from [26]) and P. duraquae MWH-MoK4 T (data from [18]).…”
Section: Ecology and Biogeographymentioning
confidence: 99%
See 1 more Smart Citation
“…These differences in pH adaptation suggests that it could have been one of the driving forces for the evolution of two lineages. However, in other genera of freshwater bacteria, species adapted to acidic and alkaline conditions are present in a single genus [50]. Genome sequencing and analysis of more strains affiliated with the GKS98 cluster, and more environmental investigations are needed to confirm the suggested ecological tendencies.…”
Section: Ecologymentioning
confidence: 99%